Evaluation of different agricultural wastes for the production of fruiting bodies and bioactive compounds by medicinal mushroom Cordyceps militaris. (29th November 2016) - Lin, Qunying; Long, Liangkun; Wu, Liangliang; Zhang, Fenglun; Wu, Shuling; Zhang, Weiming; Sun, Xiaoming
Abstract: BACKGROUND: In commercial production of Cordyceps militaris (a famous Chinese medicine), cereal grains are usually utilized as cultivation substrates. This study aimed to evaluate the efficiency of agricultural wastes as substitute materials in the low‐cost production of C. militaris . Cottonseed shells (CS), corn cob particles (CCP), Italian poplar sawdusts (IPS) and substrates spent by Flammulina velutipes (SS) were employed to cultivate C. militaris, using rice medium as control. RESULTS: CS and CCP were suitable for fruit body formation of C. militaris, with yields of 22 and 20 g per bottle respectively. Fruit bodies grown on CCP showed the highest levels of cordycepin and adenosine, up to 9.45 and 5.86 mg g −1 respectively. The content ofd ‐mannitol in fruit bodies obtained on CS was 120 mg g −1 (80% of the control group), followed by that on CCP, 100 mg g −1 . Fruit bodies cultivated on CCP displayed a high crude polysaccharide level of 26.9 mg g −1, which was the closest to that of the control group (34.5 mg g −1 ). CONCLUSION: CS and CCP are effective substrates for the production of fruit bodies and bioactive compounds by C. militaris . This study provides a new approach to decreasing the cost of C. militaris cultivation and dealing with these agricultural wastes. © 2016 Society of Chemical Industry